Sistem Rancang Bangun Alat Pemberi Pakan Otomatis Pada Ayam Petelur Berbasis IoT Menggunakan Node MCU - Muchammad Lukman Fauszan; Mochamad Choirul Fu’ad; Akhmad Solikin (FORTEI Regional VII Jawa Timur, 2022)
For breeders who own a large number of chickens, it becomes a difficult task to keep them fed around the clock. Generally, farmers sprinkle feed on the feed ticket using their hands and walk along the cage, where the laying hens are very spacious. Such activities for chicken farmers will take time and energy. Such activities for chicken farmers will take time and energy. The main controller of this system uses the MCU Node which is connected to an RTC (Real Time Clock) to adjust the feeding time of chickens in real time. This automatic tool has two parts, namely the main container serves as a place to store food reserves, equipped with a servo motor that functions to open the valve so that the feed can come out to the feed in the cage.